Kesantunan Deklaratif dalam Kegiatan Webinar Pendidikan “Peran Guru dalam Mengembangkan Pembelajaran Jarak Jauh Menyikapi New Normal #1” di Youtube - Putri, Eka Rahayu; Herwandi, Herwandi (UIR PRESS, 2021)
Webinars are seminars or meetings held virtually using certain internet-based applications. In participating in webinar activities, many types of speech that can be used by webinar participants, one of which is declarative speech. Declarative speech can be examined from various aspect, including aspect of function and the principle of politeness. This study aims to describe, analyze, and interpret declarative politeness in the educational webinar activity “The Role pf Teachers in Developing Distance Learning in the Respecting the New Normal #1” on Youtube. This research uses a descriptive method. The data analysis technique in this study used content analysis techniques. Data collection techniques used in this study were documentation techniques, listening techniques, and note-taking techniques. The data in this study are in the form of declarative speech spoken by the webinar participants. Sources of data in this study are the entire speeches of the educational webinar participants “The Role of Teachers in Developing Distance Learning in Respecting New Normal #1” which was broadcast live on June 17, 2020. The results of this study indicate the following. First, the most declarative function found in the speeches of webinar participants in educational webinar activities is the function of declaring information. Based on the data analysis of the declarative speech function, the function of declaring information is widely found because most of the contents of this webinar activity are providing information or matters relating to information about the role of teachers in developing distance learning. Second, the maxims of politeness principles found in the declarative utterances of webinar participants in educational webinar activities are maxim of appreciation and maxim of sympathy. Based on the data analysis, the maxim of politeness principle, the maxim of appreciation and the maxim of sympathy were found because the webinar participants were more likely to show respect and sympathy for the speech partner.